Congenital Membranous Stapes Footplate Producing Episodic Pressure-Induced Perilymphatic Fistula Symptoms - Matsuda, Han; Tanzawa, Yasuhiko; Sekine, Tatsuro; Matsumura, Tomohiro; Saito, Shiho; Shindo, Susumu; Usami, Shin-ichi; Kase, Yasuhiro; Itoh, Akinori; Ikezono, Tetsuo (Frontiers in Neurology, 2020)
Recent third window syndrome studies have revealed that the intact bony labyrinth and differences in the stiffness of the oval and round windows are essential for proper cochlear and vestibular function. Herein, we report a patient with a congenital dehiscence of the right stapes footplate. This dehiscence caused long-standing episodic pressure induced vertigo (Hennebert sign). At the time of the presentation, her increased thoracic pressure changes induced rupture of the membranous stapes footplate. Perilymph leakage was confirmed by imaging and a biochemical test (perilymph specific protein CTP [Cochlin-tomoprotein] detection test). Case Report: A 32-year-old woman presented with a sudden onset of right-sided hearing loss and severe true rotational vertigo, which occurred immediately after nose-blowing. CT scan showed a vestibule pneumolabyrinth. Perilymphatic fistula (PLF) repair surgery was performed. During the operation, a bony defect of 0.5 mm at the center of the right stapes footplate, which was covered by a membranous tissue, and a tear was found in this anomalous membrane. A perilymph specific protein CTP detection test was positive. The fistula in the footplate was sealed. Postoperatively, the vestibular symptoms resolved, and her hearing improved. A more detailed history revealed that for 15 years, she experienced true rotational vertigo when she would blow her nose. After she stopped blowing her nose, she would again feel normal. Discussion: There is a spectrum of anomalies that can occur in the middle ear, including the ossicles. The present case had a dehiscence of the stapes with a small membranous layer of tissue covering a bony defect in the center of the footplate. Before her acute presentation to the hospital, this abnormal footplate with dehiscence induced pathological pressure-evoked fluid-mechanical waves in the inner ear, which resulted in a Hennebert sign. When patients have susceptibility (e.g., weak structure) to rupture, such as identified in this case, PLF can be caused by seemingly insignificant events such as nose-blowing, coughing, or straining. Conclusion: This case demonstrates that PLF is a real clinical entity. Appropriate recognition and treatment of PLF can improve a patient’s condition and hence, the quality of life.